The Role of Islamic Pawnshops in Empowering the Community's Economy: A Review of Maqashid Syariah - hasyanto; Muh Taufan (Journal of Sharia, Law, and Economics, 2025)
This study aims to analyze the role of Islamic pawnshops (pegadaian syariah) in empowering the Muslim community’s economy through the perspective of maqashid shariah. Islamic pawnshops not only function as providers of interest-free collateral services but also serve as strategic instruments in promoting financial inclusion and enhancing community welfare. Employing a qualitative method based on library research, this study synthesizes various classical and contemporary literatures related to the concepts of rahn, maqashid shariah, and the dynamics of Islamic economics. The findings reveal that Islamic pawnshops have effectively implemented the principles of maqashid shariah, particularly within the dimensions of hifz al-mal (protection of wealth), hifz al-din (protection of religion), and hifz al-nafs (protection of life), through inclusive and ethical financing products. Beyond expanding access to formal financial services, Islamic pawnshops also support microenterprises, strengthen financial literacy, and instill Islamic economic values within society. This study concludes that Islamic pawnshops hold significant potential as catalysts for community-based economic development, although structural challenges such as limited geographical reach and the need for product innovation remain to be addressed. Theoretically, the study reinforces maqashid shariah as a comprehensive evaluative framework for assessing the effectiveness of Islamic financial institutions. Practically, it recommends integrating Islamic pawnshops into the national Islamic financial ecosystem through service digitalization and regulatory strengthening grounded in maqashid shariah.